â€œCINDELARASâ€ KIDS ILLUSTRATION AS A MORAL LEARNING MEDIA FOR CHILDREN - Wardani, Kemala Pintaka (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Moral learning can be taught through stories, which act as orientations and role models to stimulate understanding which then becomes the habituation and personal character of the child. In this study project moral learning is presented in stories in the form of comic books, with Cindelaras's story as example. The comic book creation process goes through several stages of the creative process namely the pre-production process, the production process and the post-production process. The main work produced was a dummy form from a comic book titled